Розподiл потенцiалу скалярного поля для “розмазаної” замкненої нуль-струни, яка прямує в площинi z = 0 - Lelyakov, O. P.; Karpenko, A. S.; Babadzhan, R.-D. O. (Publishing house "Academperiodika", 2018)
A general form for the scalar-field potential distribution has been proposed for a closed “thick” null string either collapsing or expanding in the plane z = 0. Conditions, under which the energy-momentum tensor components for a scalar field that contracts into a one-dimensional object (a circle with a varying radius) asymptotically coincide with those for a closed null string moving along the same trajectory, have been found.